Pengaruh media kartu kata bergambar dalam meningkatkan kemampuan membaca permulaan di sekolah dasar - Farida Hannum Ritonga; Aufa Aufa (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This Study alims: 1) to find out how the use of picture word calrds medial in improving the albility to start reading in clalss 1, 2) to find out how the effect of picture word calrds medial in improving the albility to start reading in clalss 1 students. The resealrch method used in this resealrch is alqualntitaltivealpproalch with Qualsi Experiment resealrch type. The independent valrialble in this resealrch is the use of illustralted word calrds while the dependent valrialble is the albility to start reading. The populaltionused is 20 experimentallclalss students alnd 20 control clalss students. The resealrchsalmpleused is salturaltedsalmple. In this study, the daltal collection technique used walsobservaltion. Tests, alnddocumentaltiondaltalwals collected by pretest, trealtment, alndpost test. Alnd the daltalalnallysis techniques calrriedout in this study were descriptive staltalticall tests, normallity tests, wilcoxon signed hypothesis tests, alnd homogeneity tests with the SPSS system. The result of this study indicaltethalt the alveralgevallue of students before the alpplicaltion of the medialwals 79,5%, while alfter the alpplicaltionvallue of students increalsed to 92%. It is alccepted. So it caln be concluded thalt this picture word walrdcalrd medialhalsal very significalnt influence in improvingalloudrealding skills in gralde 1 elementalry school, so this picture word calrd medial is very suitalble for use in gralde 1 to improve students’ start reading skills.